Harmonization of Customary Law, Green Constitution and Green Fatwa: Case Forest Burning and Land for Agriculture in Central Kalimantan - Muhammad Wahdini; Hasse Jubba; Kamsi; Achmadi; Ardi Akbar Tanjung; Ahamed Sarjoon Razick (Mazahibuna: Jurnal Perbandingan Mazhab, 2025)
Central Kalimantan is a province that often has large-scale forest and land fires. The problem is then associated with the local wisdom of the Dayak tribe as the indigenous tribe of Central Kalimantan who still carry out the manugal tradition where one of the stages is to burn land before farming. The practice of the manugal tradition includes burning land before farming with the aim of fertilizing the soil. In the realm of positive law, many environmental laws and regulations, which are then called green constitutions, regulate the anticipation of forest and land fires. In addition, Islamic law also talks a lot about the concept of environmental management, in the context of Indonesia, the Muslim community responds to various environmental issues with various responses such as issuing environmental fatwas which are then known as green fatwas. Therefore, the question arises how the green constitution and green fatwa review the manugal custom as a local wisdom or customary law. The frequent contradiction between customary law, Islamic law and positive law encourages the author to conduct research in this perspective. This research method is normative juridical using statutory and conceptual approaches. The results of this study indicate that in the perspective of green constiution from the level of the Constitution to the legislation has accommodated the custom as long as it does not cause widespread forest and land fires. In the green fatwa perspective, only MUI specifically issued a fatwa on forest and land burning through fatwa number 30 of 2016 which legally prohibits, but there are exceptions for controlled forest and land burning and aims for benefits. So that the manugal custom remains in the corridor of harmonization with the green constitution and green fatwa